A novel method to include the free surface in a CFD model of jet injection into partially-baffled mixing vessels. (23rd July 2009) - Torre, Jean-Philippe; Higgins, Peter; Xuereb, Catherine; Fletcher, David F.
A novel methodology that can be used to perform simulations of fluid jet injection into a mixing vessel with a deformed free surface is presented and validated. The idea is to first use a two-fluid model to determine the location and shape of the free surface, and then results from the simulation are used to generate a single-phase model that has the same free surface shape. Example simulations are performed using ANSYS CFX for a pilot-scale partially-baffled vessel. Application of the methodology in the study of reaction quenching is presented but it is believed that this methodology has many other possible applications involving fluid or solid injection.